A simple turn-on Schiff base fluorescence sensor for aluminum ion. Issue 31 (3rd August 2016) - Zhu, Jinli; Zhang, Yuhuan; Wang, Lun; Sun, Tongming; Wang, Miao; Wang, Yipu; Ma, Danyang; Yang, Qingqing; Tang, Yanfeng
Graphical abstract: Highlights: A simple Schiff-based fluorescence sensor for Al 3+, was synthesized. This sensor was of good selectivity and sensitivity for Al 3+ . This sensor can be used in real water and live cells. Abstract: A simple Schiff baseL derived from 2-hydroxy-naphthalene-1-carbaldehyde and benzene-1, 2-diamine, was proved to be a turn-on fluorescent probe for the recognition of Al 3+, based on photoinduced electron transfer (PET) mechanism. It exhibited a high selectivity for Al 3+ over other competing ions (e.g., Hg 2+, Ag +, Pb 2+, Cu 2+, Ba 2+, Cd 2+, Zn 2+, Ni 2+, Co 2+, Fe 2+, Fe 3+, Mn 2+, Li +, Cr 3+, Ca 2+, Mg 2+, K +, Na + ) in EtOH/HEPES buffer (95:5, v/v, pH = 7.2). The complex formation ofL –Al 3+ was determined to be 1:1 forL and Al 3+ in molar. This result was based on the Job plot, 1 H NMR titration and ESI-mass. The binding constant of the complex was 6.53 × 10 3 M −1 with a detection limit of 1.08 × 10 −7 M. The potential applications ofL to detect Al 3+ in live cells and in environmental water samples were also investigated. The results indicated thatL could be a promising probe for Al 3+ recognition.